Islamic Economic Contribution In The Age of Globalization Trend - Ivonne Ayesha; Marsinah Marsinah; Fitria Marisya; Sherly Malini; Nanang Qosim (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2023)
Conventional economics has not only weaknesses but also strengths. Its weakness mainly lies in its secular paradigm, which separates positive and normative economics, the absence of a solid relationship between micro and macroeconomics; and the neglect of moral and ethical values ​​in its descriptive and predictive functions. The advantage is the sophisticated achievement of conventional economic theories with mathematical models and calculus. The era of globalization and the phenomenon of the development trend in economics has given rise to many opportunities as well as challenges, especially in efforts to develop Islamic economics. Therefore, in the future development of the Islamic economy, apart from learning from the successes and failures of conventional economics, it is also necessary to utilize new creative and innovative approaches to truly realize an Islamic economy that is rahmatan lil'alamin in its various aspects.